A deuterium-poor water reservoir in the asteroid 4 Vesta and the inner solar system. (15th March 2021) - Stephant, A.; Wadhwa, M.; Hervig, R.; Bose, M.; Zhao, X.; Barrett, T.J.; Anand, M.; Franchi, I.A.
Abstract: Recent investigations of meteorites thought to originate from the asteroid 4 Vesta have suggested an early accretion of water on rocky bodies in the inner Solar System from a carbonaceous chondrite-like source. However, these studies have been based on the hydrogen isotope compositions (δD) of late-crystallizing apatite grains in eucrites that likely do not record the primary magmatic composition. We have determined the δD and H2 O concentrations in some of the earliest-formed silicates (clinopyroxenes) from several eucrites with the goal of constraining the hydrogen isotope composition of their source reservoir on their parent body. The H2 O concentrations in clinopyroxenes from eucrites Juvinas, Stannern and Tirhert range from 5 to 18 μg/g, with a weighted average δD of –263 ± 70‰. Their apatites and whitlockites exhibit a higher weighted average δD of –165 ± 73‰, possibly as a result of H2 degassing during or after phosphate crystallization. Thermal metamorphism of these eucrites has most probably resulted in the loss of H, and an increase in their original δD values. While the weighted average δD value for the eucrite clinopyroxenes reported here is inferred to reflect an upper limit for the isotopic composition of the silicate mantle reservoir on their parent asteroid 4 Vesta, the average δD value of Stannern clinopyroxenes is considered to be closest to the initial δD of the source mantle (i.e., –373 ± 127‰), which is lighter than that of Earth's depleted upper mantle and most carbonaceous chondrites. We suggest that at least some of the water in 4 Vesta (and possibly other rocky bodies in the inner Solar System) was derived from a relatively deuterium-poor reservoir in the protosolar nebula, which was incorporated into planetesimals formed early in Solar System history.